إجراءات المسترشد بالله لإضعاف حكم السلاجقة وأثرها على الخلافة العباسية (512-529 هـ./1118-1134 م.) - مصطاف، ثامر نعمان (جامعة ذي قار - كلية الآداب, 2021)
اختلفت سياسة الخليفة المسترشد بالله العباسي عن سلفه من الخلفاء في التعامل مع السلاطين والأمراء السلاجقة، فقد عمل عند تقلده مهام الحكم على استعادة هيبة واستقلال الخلافة وتقوية نفوذها من خلال الاعتماد على جماهير الناس الذين التفوا حوله وآزروه في محنته مع السلاجقة، فقام بمنع أي تدخل من جانب السلاطين في أمور الخلافة، بل وعمل بالتدخل في شؤون السلطنة السلجوقية بحجة الإصلاح، كما دخل بمعارك مع جيوش السلاطين داخل العراق وخارجه، إلا أن سياسة الغدر والخديعة التي انتهجها الأمراء السلاجقة قد أفشلت مشروعة بالتحرر من تسلط السلاجقة. اشتمل البحث على مقدمة وثلاثة مباحث، وخاتمة. تطرقنا في المبحث الأول إلى الأحوال العامة التي رافقت تولي المسترشد بالله الحكم، وأهم المشاكل التي واجهت الخلافة ومنها تمرد بعض الأمراء المحليين وآثارها على الخلافة. وخصص المبحث الثاني لإجراءات الخليفة المسترشد بالله لإضعاف نفوذ السلطان محمود وأثر ذلك في العلاقة بينهما. ودرس المبحث الثالث جهوده لإضعاف وتحجيم دور السلطان مسعود حتى سنة 529 ه/ 1134 م، وأثرها على الخلافة العباسية. وجاءت الخاتمة لتسجل أهم النتائج التي توصل إليها البحث. The policy of the caliph “Almustarshad Biallah” differed from his predecessors in dealing with the sultans and the Seljuk princes. When he became the ruler, he was determined to restore the prestige and independence of the Caliphate and strengthen its influence by relying on the masses of people who had gathered around him and supported him in his ordeal with the Seljuks. He not only prevented any interference of the sultans in matters of the caliphate but also he intervened in the affairs of the Seljuk Sultanate claiming he is after reform. He also engaged in battles with the armies of the sultans inside and outside Iraq, but the policy of treachery and deception adopted by the Seljuq princes failed his emancipation project from the domination of the Seljuks. The research includes an introduction, three sections, and a conclusion. The first section deals with the general circumstances when Almustarshad Biallah took the rule: and it also deals with the most important problems facing the caliphate, including the rebellion of some local princes and their effects on the caliphate. The second section is dedicated to the actions of Almustarshad Biallah to weaken the influence of Sultan Mahmud and its impact on their relationship. The third section studies his efforts to weaken and reduce the role of Sultan Masood until 529 A.H./1134 A.D. and their impact on the Abbasid Caliphate. The conclusion records the most important findings of the research.
الجزء الثاني. مارس 2021
Keywords: التاريخ الإسلامي -- المسترشد بالله، الفضل بن أحمد بن المقتدي، خليفة عباسي، ت. 529 هـ. -- الأنظمة الحاكمة -- الدولة السلجوقية -- العصر العباسي